A longitudinal survey of African animal trypanosomiasis in domestic cattle on the Jos Plateau, Nigeria: prevalence, distribution and risk factors - Majekodunmi, Ayodele O (BioMed Central, 2013)
BACKGROUND: Trypanosomiasis is a widespread disease of livestock in Nigeria and a major constraint to the rural economy. The Jos Plateau, Nigeria was free from tsetse flies and the trypanosomes they transmit due to its high altitude and the absence of animal trypanosomiasis attracted large numbers of cattle-keeping pastoralists to inhabit the plateau. The Jos Plateau now plays a significant role in the national cattle industry, accommodating approximately 7% of the national herd and supporting 300,000 pastoralists and over one million cattle. However, during the past two decades tsetse flies have invaded the Jos Plateau and animal trypanosomiasis has become a significant problem for livestock keepers. METHODS: In 2008 a longitudinal two-stage cluster survey on the Jos Plateau. Cattle were sampled in the dry, early wet and late wet seasons. Parasite identification was undertaken using species-specific polymerase chain reactions to determine the prevalence and distribution bovine trypanosomiasis. Logistic regression was performed to determine risk factors for disease. RESULTS: The prevalence of bovine trypanosomiasis (Trypanosoma brucei brucei, Trypanosoma congolense savannah, Trypanosoma vivax) across the Jos Plateau was found to be high at 46.8% (39.0 – 54.5%) and significant, seasonal variation was observed between the dry season and the end of the wet season. T. b. brucei was observed at a prevalence of 3.2% (1% – 5.5%); T. congolense at 27.7% (21.8% - 33.6%) and T. vivax at 26.7% (18.2% - 35.3%). High individual variation was observed in trypanosomiasis prevalence between individual villages on the Plateau, ranging from 8.8% to 95.6%. Altitude was found to be a significant risk factor for trypanosomiasis whilst migration also influenced risk for animal trypanosomiasis. CONCLUSIONS: Trypanosomiasis is now endemic on the Jos Plateau showing high prevalence in cattle and is influenced by seasonality, altitude and migration practices. Attempts to successfully control animal trypanosomiasis on the Plateau will need to take into account the large variability in trypanosomiasis infection rates between villages, the influence of land use, and husbandry and management practices of the pastoralists, all of which affect the epidemiology of the disease.